RECHTSVINDING METHOD OF JUDGES IN FILLING LEGAL EMPTY "STUDY OF APPROACHES IN LEGAL DISCOVERY" - Apipuddin Apipuddin (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
One of the important stages in the world of justice is the stage of legal discovery by judges to resolve cases that are being disputed. Many new cases emerge and escape from existing legal rules resulting in a legal vacuum, while judges must not refuse to examine, try and decide on cases that come to them on the grounds of lack of law or unclear regulation. Judges are required to find the law in resolving disputes. On the other hand, the implementation of procedural law shows a formalistic, positivistic, and textualist image, and the condition is assumed to be a part that contributes to the method of legal discovery by judges and the quality of decisions produced. In a pluralistic state of law such as in Indonesia, of course, the legal discovery of justice must be based on the perspective and method of studying legal science. The study must not stop let alone rely only on the perspective of positive legal ansicht. It is important for judges to accommodate perspectives, approaches, theories, rules, and other legal norms such as Islamic Law with the Istinbath Al-Ahkam method and Customary Law with their very varied and characteristic views on the law. The comprehensive review is expected to have an impact on the inclusiveness of judges in harmonizing all approaches and legal systems that apply in their decisions and does not consider the position of the text of the legislation to be final and free from penetration of the interpretation of reason that develops in accordance with the behavior of the community, which is very dynamic.